The Effect of Show and Tell, Role-Play and Storytelling on Speaking Skills: Meta-analysis - Enma Oktaviani; Ilham Ilham; Lukman Lukman; Samson Olusola Olatunji; Nicole Whitworth (Journal of Languages and Language Teaching, 2024)
Show and tell, role-play, and storytelling are all enjoyable speaking practice approaches for educators to utilize when teaching English. Therefore, the goal of this study is to assess the efficacy of the Show-and-Tell, Role-Play, and Storytelling methods for improving English speaking skills. The results of this study were obtained using JASP software, and 60 research findings met the criteria for the analysis, which shows a significant statistical impact from the three speaking approaches. In the Show-and-Tell method, the effect size value was 1.09 (High Effect), in the Role-Play method it was 1.13 (Very High Effect), and in the Storytelling method it was 1.34 (Very High Effect). However, Storytelling has a greater impact than the other methods. Furthermore, this study suggests that research published in 2022 has the largest effect, with 1,371 (Very High Effect). Meanwhile, analyzing the number of participants, it is clear that a study with more than 52 persons has the biggest impact, with an estimated value of 1.257 (Very High Effect). Among the methods, Story-Telling had a higher influence than the other methods in teaching English speaking skills. In conclusion, this meta-analysis provides strong evidence supporting the effectiveness of the Show-and-Tell, Role-Play, and Story-Telling methods in teaching English speaking skills. The findings underscore the need for educators to incorporate these methods into their pedagogical strategies to enhance students’ English speaking skills.